THE IMPACT OF PSYCHOSOMATIC INTERVENTIONS ON CARDIOVASCULAR REHABILITATION IN POST-COVID-19 PATIENTS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background and Rationale. Recent studies indicate a 30–60% increase in cardiovascular risk following COVID-19. This is driven by two main mechanisms: Physical Injury: Direct viral damage, microvascular inflammation, and autonomic nervous system (ANS) instability.Psychosomatic Factors: Anxiety and depression (observed in 35–40% of patients) act as initiators for ischemic events and panic attacks, which patients often mistake for heart attacks. The Biological-Spiritual Dependency (The Stress Axis) Psychosomatic factors aggravate heart disease through the chronic release of stress hormones (Adrenaline and Cortisol). This leads to: Increased cardiac workload and vascular tension. Chronic inflammation, which deepens psychological depression, creates a vicious cycle.